P 33 Changes in functional connectivity relate to modulation of cognitive control by subthalamic stimulation. (May 2022) - Achtzehn, J.; Irmen, F.; Horn, A.; Güttler, C.; Horn, A.; de Almeida Marcelino, A.L.; Wenzel, G.; Schneider, G.H.; Neumann, W.J.; Kühn, A.A.
Abstract : Introduction Using cognitive control, humans can flexibly influence behavior based on set goals, which includes overriding impulses by inhibiting automatic responses in a conflicting environment. The basal ganglia have been hypothesized as an integral part in a cortico-subcortical network that modulates inhibitory control in both motor and non-motor domains. Subthalamic (STN) deep brain stimulation (DBS) in Parkinson's disease (PD) patients not only improves kinematic parameters of movement but also modulates cognitive control in the motor and non-motor domain, especially in situations of high conflict. Materials & Methods During DBS ON and OFF conditions, we conducted a visuomotor task in 14 PD patients who previously underwent resting-state functional MRI (rs-fMRI) acquisitions DBS ON and OFF. In the task, participants had to move a cursor with a pen on a digital tablet either towards (automatic condition) or in the opposite direction (controlled condition) of a target. Behaviorally, the first main outcome parameter was reaction time, and specifically, the difference in reaction time between automatic and controlled condition that reflects the additional time associated with engagement of cognitive control. Furthermore, average movement velocity ON vs. OFF DBS in automatic and controlled trials was assessed. Analysis of the imaging data focused on STN DBS induced modulation of rs-fMRI connectivity as a function of changes in behavior ON vs. OFF DBS and was estimated using link-wise network-based statistics within an a-priori defined network parcellation with 7 bihemispheric regions of interest (STN, internal/external pallidum (GPi and GPe), striatum, motor thalamus (VAn, VAp, VLd/VLv nuclei combined), motor and premotor cortices, supplementary motor area (SMA) and pre-SMA). Results Behavioral results showed diminished reaction time adaptation under DBS, i.e., PD patients ON DBS slowed down significantly less in the controlled condition compared to the automatic condition than they did OFF DBS. Additionally, pen-to-target movement velocity was increased under DBS in both automatic and controlled condition. Resting-state imaging data analysis revealed that DBS-induced reaction time reduction was associated with attenuated functional connectivity between cortical motor areas, basal ganglia and thalamus. On the other hand, increased movement velocity ON DBS was associated with stronger pallido-thalamic connectivity. Conclusion These findings suggest that DBS-induced decoupling of a motor cortico-basal ganglia network underlies impaired inhibitory control in PD patients undergoing subthalamic DBS and highlight the concept of functional network modulation through DBS. Understanding the connectivity basis of nonmotor changes in PD patients treated with DBS has a high clinical relevance, since network modulation may be fine-tuned with advancing therapeutic developments such as adaptive stimulation.